Transport Deficiency Is the Molecular Basis of Candida albicans Resistance to Antifungal Oligopeptides - Schielmann, Marta; Szweda, Piotr; Gucwa, Katarzyna; Kawczyński, Marcin; Milewska, Maria J.; Martynow, Dorota; Morschhäuser, Joachim; Milewski, Sławomir (Frontiers in Microbiology, 2017)
Oligopeptides incorporating N3-(4-methoxyfumaroyl)-L-2,3-diaminopropanoic acid (FMDP), an inhibitor of glucosamine-6-phosphate synthase, exhibited growth inhibitory activity against Candida albicans, with MIC values in the 0.05 – 50 µg mL-1 range. Uptake by the peptide permeases was found to be the main factor limiting an anticandidal activity of these compounds. Di- and tripeptide containing FMDP (F2 and F3) were transported by Ptr2p/Ptr22p peptide transporters and FMDP-containing hexa-, hepta- and undecapeptide (F6, F7 and F11) were taken up by the OPT oligopeptide permeases, preferably by Opt2p/Opt3p. A phenotypic, apparent resistance of C. albicans to FMDP-oligopeptides transported by OPT permeases was triggered by the environmental factors, whereas resistance to those taken up by the PTR system had a genetic basis. Anticandidal activity of longer FMDP-oligopeptides was strongly diminished in minimal media containing easily assimilated ammonium sulfate or L-glutamine as the nitrogen source, both known to downregulate expression of the OPT genes. All FMDP-oligopeptides tested were more active at lower pH and this effect was slightly more remarkable for peptides F6, F7 and F11, compared to F2 and F3. Formation of isolated colonies was observed inside the growth inhibitory zones induced by F2 and F3 but not inside those induced by F6, F7 and F11. The vast majority (98%) of those colonies did not originate from truly resistant cells. The true resistance of 2% of isolates was due to the impaired transport of di- and to a lower extent, tripeptides. The resistant cells did not exhibit a lower expression of PTR2, PTR22 or OPT1-3 genes, but mutations in the PTR2 gene resulting in T422H, A320S, D119V and A320S substitutions in the amino acid sequence of Ptr2p were found.